Challenges for meaningful interpersonal communication in a digital era - Elza Venter (HTS Teologiese Studies/Theological Studies, 2019)
As digital tools and social networks became the main mode of interaction for many people, interpersonal communication has changed. Computer-mediated communication (CMC) has become more important than face-to-face communication in many contexts. Younger generations prefer CMC. Personal interaction normally consists of verbal and non-verbal communication. Computer-mediated communication lacks traditional non-verbal cues, which may cause misunderstandings, influencing meaningful interpersonal communication. Because of a lack of face-to-face communication, people often present an idealised version of themselves, thus becoming less inhibited involving more inappropriate self-disclosure on, for instance, social networks. The research question for this literature review was whether communicating with others mainly through digital means without adequate non-verbal cues would influence meaningful interaction between people. This study used the cues-filtered-out approach and the social presence theory with a literature review to get some clarity on the above question. The premise of the author was that because of the lack of non-verbal cues, CMC messages could influence the understanding of emotions and attitudes, thus compromising meaningful communication and personal understanding of the other. The outcome was that in today’s world people have to use CMC, but for meaningful interpersonal communication, they should try to combine it with face-to-face interaction.